2012
DOI: 10.5897/ijps11.1748
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cobalt (II) ions from aqueous solution by using alternative adsorbent industrial red mud waste material

Abstract: This study on the removal of cobalt ions from aqueous solutions by red mud was conducted in batch condition. Its objective was to investigate the possibility of using red mud waste material as an alternative to high cost commercial adsorbent materials for the removal of cobalt from aqueous solution. In this study, batch experiments were carried out for the adsorption of cobalt onto red mud industry waste. The red mud waste material was successfully used for the removal of cobalt ion from aqueous solution and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…The reduction in the number of ions removed with increasing temperature showed that adsorption was exothermic and favored a low temperature. Our results are in complete agreement with those of other scholars [ 51 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 94%
“…The reduction in the number of ions removed with increasing temperature showed that adsorption was exothermic and favored a low temperature. Our results are in complete agreement with those of other scholars [ 51 , 53 , 54 ].…”
Section: Resultssupporting
confidence: 94%
“…Турски црвени муљ (Seydisehir Aluminum Plant, Konya, Turkey), третиран кувањем вишеструко испраног муља у 10% Hcl, показао се као успешан сорбент јона Cu и Co из синтетичких водених раствора и загађене речне воде, а примењена техника оцењена је као индустријски примењива и одржива. Ефикасност сорпције повећавала се са повећањем времена, температуре, pH и масе сорбента, а смањила са повећањем почетне концентрације адсорбата (Nadaroglu et al 2010;Nadaroglu et al 2012). Ефикасност уклањања металних јона помоћу третираног турског црвеног муља у великој мери зависила је од pH средине (Сл.…”
Section: употреба црвеног муља за издвајање катјона тешких металаunclassified
“…12.9. Variation of cobalt ions concentration in polluted water and synthetic solution after red mud treating (Nadaroglu and Kalkan 2012) Црвени муљеви са различитих локалитета испитивани су као потенцијални сорбенти за уклањање јона никла из водених раствора и отпадних вода (Apak and Ünseren 1987;Zouboulis and Kydros 1993;Lópezet al 1998 Иницијална концентрација јона метала снажно је утицала на сорпциону кинетику и равнотежно време. Додатак од 5 g/l RBRM, при иницијалном pH 5, изазвао је 100%-но уклањање из раствора концентрације 10 -4 -510 -4 mol/l, док се са даљим повећањем концентрације Ni 2+ јона до 810 -3 mol/l, ефикасност смањила до 26% (Сл.…”
Section: употреба црвеног муља за издвајање катјона тешких металаunclassified
See 1 more Smart Citation
“…The adsorption isotherms for cobalt and chromium removal were studied using the best conditions obtained from experimental work with a constant PA6/CaO-gAA amount of 30 mg/20 mL of adsorbate, a metal ions concentration of 10 ppm at pH 5, and a constant magnetic stirring time of 150 min, and the temperature of the solution was 30°C. Afterword; The Langmuir and Freundlich isotherms were used to fit the obtained data [51].…”
Section: Adsorption Isotherms Modelsmentioning
confidence: 99%